PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS V - Hartati S. Husin; Harni Jusuf; Asriyati Nadjamuddin (Al-mujahidah, 2026)
This study aims to determine the application of the cooperative learning model of make and match type can improve student learning outcomes in the subject of Indonesian language class V SDN 11 Limboto Barat. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 25 students consisting of 16 female students and 9 male students. Based on the assessment of learning activities in cycle II, there were 25 students who obtained good learning outcomes in understanding reading material, while 12 people obtained fairly good results. The increase in student learning outcomes in this cycle II activity can be seen from the average value achieved by students based on the indicators assessed, the average achieved was in the range of 97 values. In the second cycle, the effectiveness of using the Make A Match method increased, with the average value of student activity reaching 97% and all students successfully meeting the Learning Technical Completion Criteria (KKTP) with an average value of 84.51. However, there are still aspects that need to be improved, such as students' courage to ask questions and active participation in group discussions, which are each at 75%.